Risk Factors for Midline Catheter Failure: A Secondary Analysis of an Existing Trial - Bahl A; Johnson S; Mielke N; Chen NW (Dove Medical Press, 2022)
Amit Bahl,1 Steven Johnson,1 Nicholas Mielke,2 Nai-Wei Chen3 1Department of Emergency Medicine, Beaumont Hospital, Royal Oak, MI, USA; 2Oakland University William Beaumont School of Medicine, Rochester, MI, USA; 3Research Institute, Beaumont Hospital, Royal Oak, MI, USACorrespondence: Amit Bahl, Department of Emergency Medicine, Beaumont Hospital, Royal Oak, 3601 13 Mile Road, Royal Oak, MI, 48073, USA, Email Amit.bahl@beaumont.eduObjective: While midline catheters (MCs) are considered to be a reliable form of vascular access, up to 25% of the placements culminate in failure. We aimed to explore risk factors for MC failure.Methods: We performed an analysis of existing randomized controlled trial data involving a comparison of two midline catheters. The study aimed to assess risk factors related to MC failure, including patient, procedure, catheter, and vein characteristics. Cox regression was used for univariable and multivariable analyses to evaluate the association between characteristics and MC failure.Results: Among 191 patients that were included in this secondary analysis, more patients were female (114/191 [59.7%]) and average age was 60.2 (SD = 16.7) years. Clinical indications for MC placement included antibiotics (60.7%), difficult venous access (32.5%), or both (6.8%). In a univariable Cox regression analysis, the increase in pulse rate (HR 1.02; 95% CI, 1.00- 1.04; P=0.02), temperature ≥ 38°C (HR 5.59; 95% CI, 1.96- 15.94; P=0.001), oxygen saturation < 93% (HR 2.91; 95% CI, 1.03- 8.24; P=0.04), norepinephrine in dextrose infusion (HR 2.41; 95% CI, 1.17- 4.97; P=0.02) and cephalic vein insertion (HR, 2.47; 95% CI, 1.09- 5.57; P=0.03) were all associated with higher risk of MC failure. In a multivariable Cox model, difficult venous access (aHR 2.05; 95% CI, 1.04- 4.05; P=0.04) and norepinephrine in dextrose (aHR 2.29; 95% CI, 1.09- 4.82; P=0.03) was associated with catheter failure.Conclusion: Elevated pulse rate, decreased oxygen saturation level, temperature ≥ 38°C, and norepinephrine use were each associated with an increased risk of MC failure. These factors should be considered when selecting the most appropriate vascular access device for individual patients. Additionally, the cephalic vein insertion has the highest risk for MC failure and other access points could be preferentially considered.Keywords: midline catheter, complications, risk factors, midline catheter failure, vesicants, vascular access